2014
DOI: 10.1016/j.agee.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment of the reuse of two discrete treated wastewaters for the irrigation of tomato crop on the soil geochemical properties, fruit safety and crop productivity

Abstract: Advanced tertiary treatment and disinfection technologies have enabled the production of wastewater (WW) with quality complying with the established criteria for reuse in agriculture. This study assessed the impacts of tomato crop irrigation with two qualitatively distinct treated WW effluents, as compared to control tubewell water (TW) irrigation, on the soil geochemical properties, tomato fruit safety and crop productivity. The treated effluents reused for irrigation were produced in two Municipal Wastewater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 47 publications
5
29
0
Order By: Relevance
“…Our results are in agreement with other recent studies that have shown low impact for the microbial contamination of tomato crops irrigated by treated secondary wastewaters (Cirelli et al, 2012;Christou et Gatta et al, 2014). This will be due to several factors, such as: the drip irrigation system and mulching system adopted, and the effects of UV radiation exposure on the fruit and leaf surfaces.…”
Section: Qualitative Traits and Microbial Pollution Of The Tomato Plasupporting
confidence: 82%
See 1 more Smart Citation
“…Our results are in agreement with other recent studies that have shown low impact for the microbial contamination of tomato crops irrigated by treated secondary wastewaters (Cirelli et al, 2012;Christou et Gatta et al, 2014). This will be due to several factors, such as: the drip irrigation system and mulching system adopted, and the effects of UV radiation exposure on the fruit and leaf surfaces.…”
Section: Qualitative Traits and Microbial Pollution Of The Tomato Plasupporting
confidence: 82%
“…Some studies have investigated the influence of irrigation with treated wastewater on tomato crop yields, but there remains the need to better define the full effects on the fruit quality parameters and the acceptable levels of biological contamination (Aiello et al, 2007;Christou et al, 2014;Gatta et al, 2014). For this purpose, the present study was designed to evaluate the effects of two water irrigation sources, as the groundwater (GW) control, and treated agro-industrial wastewater (SW), on the main quality parameters and microbiological safety of processing tomato fruit.…”
Section: Introductionmentioning
confidence: 99%
“…While several previous studies have evaluated the effect of application of raw WW to irrigate crops (Fattal et al, 1986;Minhas et al, 2006;Rosas et al, 1984) and determined it unfit, few studies have examined the implications of applying TWW for irrigation of vegetable crops (Christou et al, 2014;Cirelli et al, 2012;Forslund et al, 2010Forslund et al, , 2012Martinez et al, 2013). Treatment of WW is intended to reduce organic matter, nitrogen, and microbial contaminants (Bitton, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…In fact, reports from around the world indicate that irrigation with TWW presents no greater risk than irrigation with potable water (Bichai et al, 2012;Christou et al, 2014;Cirelli et al, 2012;Forslund et al, 2012Forslund et al, , 2010Jang et al, 2013;Martínez et al, 2013;Shuval, 2010). However, these reports rely either on epidemiological data (reviewed in Shuval, 2010) or mainly on fecal indicator bacteria (FIB) such as coliforms or Escherichia coli to assess possible health risks (Bichai et al, 2012;Christou et al, 2014;Forslund et al, 2012Forslund et al, , 2010Jang et al, 2013), neglecting major pathogen groups such as viruses and protozoa. The lack of correlation between pathogens and FIB, currently used in microbiological monitoring standards (Bitton, 2011;Edberg et al, 2000;WHO, 2006), is well established (Harwood et al, 2005;Ottoson et al, 2006;Payment et al, 2001) and may lead to under-or over-estimation of the risks to public health.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, methods that increase the probability of direct contact between waste-water and edible part of plants (e.g., furrow irrigation) seem to promote greater contamination of plants than subsurface drip irrigation (Song et al, 2006a). However, Christou et al (2014) reused a tertiary treated effluent for irrigation of tomato crops and did not find evidences of microbiological contamination of the edible parts.…”
Section: Risk Of Dissemination Of Pathogens Through Wastewater Reusementioning
confidence: 98%